Maarsbergen. From deanery to castle (Bulletin KNOB, 2003)
Maarsbergen castle is one of the few large houses in the range of hills called 'Utrechtse Heuvelrug' that are still privately occupied. The history of the house dates back to 1134. It was built as deanery of monastic outbuildings of the abbey of Berne. In 1656 Maarsbergen passed into private hands and continued to be so up to the present day.On the basis of drawings and maps from the 17th century onwards the history of the historical building and its surroundings were reconstructed. Some building-historical research carried out in 1998 shed light on the oldest physically present building mass and confirmed renovations that were to be inferred from historical representations. Notarial deeds clarified and specified the sales and income for the owners.However, with the exception of those of 1613, inventories could not be retrieved, so that the question how people lived at Maarsbergen before the 20th century could not be answered. Nor were direct data available, such as building specifications before the 20th century. In this respect Maarsbergen does not differ from most houses in the Utrecht range of hills.In 1882 the Godin de Beaufort family acquired Maarsbergen. Just as their predecessors they renovated and improved the house. Unlike their predecessors, they did not exchange these renovations and contemporary improvements for a more modern perception of living later on.The historical addition of the two towers dates from 1930. Since this date their furnishing has hardly been altered. In this respect Maarsbergen does differ from the other houses in the Utrecht range of hills. It is unique and exceptional that the historical layout, fitting up as well as the furniture of a house have been preserved, are appreciated and still used.The house is a historical record from which the history of the 15th to 20th century can be read. The same applies for the park. Underneath the 19th-century landscape park the structure of the 17th-century layout is still visible.Particularly because the country estate is privately owned, this history is respected and maintained by the way of management. This requires quite some effort, resourcefulness and unconditional devotion on the part of the owners. If this should no longer be the case, it will mean the end of a 'complete' country estate, a place where the living culture can still be experienced in all its facets.